EASTERN MYSTICISM AND TIMOTHY LEARY: HUMAN BEYOND THE CONVENTIONAL REALITY - T. V. Danylova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Introduction. The complex multifaceted essence of human as a biological, psychological, social being has attracted the attention of researchers and has caused hot debates during centuries. Still now, human being, her/his nature requires a broader understanding in the context of the synthesis of long-standing philosophical, psychological, religious traditions and contemporary sciences. Purpose. This paper aims to explore the phenomenon of human being through the lens of the Eastern philosophy and T. Leary’s transpersonal perspective. Methodology. Exploratory research design was used for conducting this study. The author has used philosophical hermeneutics, secondary data collected from reports, journals, and periodicals along with own transpersonal experience. Theoretical basis and results. The essence of Eastern worldview is an awareness of unity and coherence of all things and phenomena. All things are the interdependent and interrelated parts of the One Whole: they are the different manifestations of the same unconditional reality. This is Tao for Taoists, Dharmakaya for Buddhists, Brahman for Hindus. These non-dualistic traditions emphasize: we have to transcend our dual thinking in order to perceive true nature of our inner self and to achieve the state of the absolute unity with everything that exists. “Subject – object” duality is illusory. Being disintegrated from the Oneness, a human is dissociated into different parts. The goal of a new interpretation of a human is to reintegrate these poles and transcend them. Merely theoretical approach to the problem of reintegration is insufficient. Reintegration requires a vivid experience of the “liberation” – the experience of enlightenment. This is a transpersonal experience that overcomes our common perception and goes beyond the usual “body-mind” frame. This experience was breathtakingly described by T. Leary. Experimenting with psilocybin and LSD, T. Leary was astonished that creativity was organically based; that human body contained billions of universes; and that human himself was the movement of various forms of energy. T. Leary proposed his own theory of evolution. Originality. The expansion of human horizons leads us to the new understanding/interpretation of a human being. Bringing the Eastern spiritual traditions, which perceive all objects and phenomena as various interrelated aspects of a single supreme reality, transpersonal psychology and modern sciences together, contemporary philosophers are able to design and develop a new approach to a human that will bridge the gap between different interpretations of a human being. T. Leary’s ideas resonate with both quantum physics and the Eastern philosophy. In the 21st century, T. Leary’s ideas are relevant again. Conclusion. The Eastern spiritual teachings and transpersonal experience put the human problem in a completely different context. It induces us to switch from identifying human beings with the body, mind, ego to embracing them as whole organisms interwoven into the fabric of universal entity. This holistic approach, according to which a human is an undivided, alive and organic, ideal and material being, may be seen as a launching pad for a new transdisciplinary paradigm.